2008
DOI: 10.1111/j.1475-1313.2008.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of emotional facial expressions on binocular rivalry

Abstract: Three experiments investigated whether emotional information influences perceptual dominance during binocular rivalry. In Experiment 1, rival emotional and neutral faces in the background were coupled with grating stimuli in the foreground. Results showed that gratings paired with emotional faces dominated over those paired with neutral faces. In Experiment 2, emotional and neutral faces were presented dichoptically, without being paired with other stimuli. Dominance of emotional faces was observed. Fusion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 53 publications
5
63
0
Order By: Relevance
“…Although we cannot identify the underlying mechanisms with our data, the study design used here has several methodological advantages over previous binocular rivalry studies which have examined emotional inferences (see e.g., Alpers & Pauli, 2006;Bannerman et al, 2008;Blake, 2001;Walker, 1978). Because we compared the perception between two groups (which only differed in their emotional responses to the cues), this eliminates nearly all influences of the stimulus material beyond semantic (emotional) picture content.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although we cannot identify the underlying mechanisms with our data, the study design used here has several methodological advantages over previous binocular rivalry studies which have examined emotional inferences (see e.g., Alpers & Pauli, 2006;Bannerman et al, 2008;Blake, 2001;Walker, 1978). Because we compared the perception between two groups (which only differed in their emotional responses to the cues), this eliminates nearly all influences of the stimulus material beyond semantic (emotional) picture content.…”
Section: Discussionmentioning
confidence: 94%
“…During the last decade, several binocular rivalry studies have shown that the (emotional) content of a stimulus affects the extent to which it predominates in awareness (Alpers & Pauli, 2006;Sheth & Pham, 2008). More precisely, aversively conditioned cues (Alpers, Ruhleder, Walz, Mühlberger, & Pauli, 2005), emotional scenes (Alpers & Pauli, 2006), emotional facial expressions (Alpers & Gerdes, 2007;Bannerman, Milders, de Gelder, & Sahraie, 2008;Yoon, Hong, Joormann, & Kang, 2009), as well as faces associated with affective social information (Anderson, Siegel, Bliss-Moreau, & Barrett, 2011) predominate in conscious awareness over neutral information.…”
Section: Introductionmentioning
confidence: 99%
“…For attention to drive such an effect, it would require attention to features that are perceptually suppressed. There is indeed evidence that behaviorally relevant stimuli, which may attract attention more than neutral stimuli, can break through perceptual suppression faster (Alpers & Pauli, 2006; Anderson, Siegel, Bliss-Moreau, & Barrett, 2011; Bannerman, Milders, de Gelder, & Sahraie, 2008; Yang, Zald, & Blake, 2007). Our results indicate that exogenous attentional cues may drive attention to suppressed features, providing further evidence for the dissociation of attention and consciousness (Koch & Tsuchiya, 2007; Lamme, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…One example is binocular rivalry, in which different stimuli are simultaneously presented to each eye but only one of them usually reaches consciousness at a particular time. A number of studies have revealed that, during binocular rivalry, emotional stimuli preferentially access conscious perception with respect to neutral stimuli (e.g., Alpers & Pauli, 2006; Bannerman, Milders, De Gelder & Sahraie, 2008). This finding reinforces the idea of preferential automatic access to attentional resources by emotional stimuli.…”
Section: Introductionmentioning
confidence: 99%